Implementation of DRTA (Directed Reading Thinking Activity) Strategy on Reading Comprehension Skill Student Class V Muhammadiyah Elementary School 6 Pekanbaru - Kurniaman, Otang; Noviana, Eddy (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Indonesian language learning in elementary schools is aimed at improving students language skills to communicate well and correctly, both verbal and written.The purpose of this research is to find out the implementation of learning with DRTA strategy in reading comprehension skills of students in elementary school.This research uses descriptive qualitative research method with stages is pre-field stage and field work stage. The results of the research in the pre-field stage showed that the development of teacher learning equipment to be applied in the learning is good and in suitable with the assessment indicators.At the stage of field work, the common stages of learning despite into three stages that is beginning activities learning, core activities learning and final activities learning with learning steps: (1) make predictions based on title instructions; (2) make predictions from the image instructions; (3) recite reading material; (4) assess the accuracy of the prediction and adjust the prediction.Based on the implementation of research and data analysis, it can be seen that reading comprehension with DRTA strategy can be said sufficient with indicator that most of student have been able to reach KKM value.